2015
DOI: 10.1534/g3.114.016469
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetics of Migration-Related Traits in Rainbow and Steelhead Trout

Abstract: Rainbow trout (Oncorhynchus mykiss) exhibit remarkable life history diversity throughout their native range, and among the most evident is variation in migratory propensity. Although some populations and ecotypes will remain resident in freshwater habitats throughout their life history, others have the ability to undertake tremendous marine migrations. Those that migrate undergo a suite of behavioral, morphological, and physiological adaptations in a process called smoltification. We describe a quantitative ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 73 publications
3
39
0
Order By: Relevance
“…Hecht et al . () found a modal h 2 estimate of 0.61 (0.39–0.77) for life history in the same hatchery lines but using a larger pedigree. They also found significant genetic correlations of life history with growth rate, size at age, condition factor and morphological traits, which themselves showed moderate heritabilities.…”
Section: Genetic and Environmental Determinants Of Facultative Migrationmentioning
confidence: 93%
See 1 more Smart Citation
“…Hecht et al . () found a modal h 2 estimate of 0.61 (0.39–0.77) for life history in the same hatchery lines but using a larger pedigree. They also found significant genetic correlations of life history with growth rate, size at age, condition factor and morphological traits, which themselves showed moderate heritabilities.…”
Section: Genetic and Environmental Determinants Of Facultative Migrationmentioning
confidence: 93%
“…() found that a combination of MAR genotype and genetic sex predicted 45% of the life‐history variation in O. mykiss , but that resident genotypes could give rise to migrants. MAR genes have been associated with important traits including smoltification, growth rate, developmental rate, survival in seawater and out‐migration of juveniles (Doctor et al ., ; Hale et al ., ; Hecht et al ., ; Pearse et al ., ; Phillis et al ., ). An O. mykiss population (Scott Creek, California; 37° 28′ N, 121° 56′ W), which was translocated in 1910 from below to above a waterfall, was shown to have undergone a 49% reduction in the frequency of the MAR migratory genotype (Pearse et al ., ).…”
Section: Genetic and Environmental Determinants Of Facultative Migrationmentioning
confidence: 99%
“…Previous studies have suggested that heritable variation for migration and seawater adaptation exists within multiple salmonid species (see Carlson and Seamons (2008)) for a review), including variation between anadromous sockeye and resident Kokanee Salmon (Oncorhynchus nerka; Foote, Wood, Clarke, & Blackburn, [1992]). Moreover, genetic correlations for characters related to migration vs. residency in rainbow and steelhead trout (Oncorhynchus mykiss) suggest that there is a genetic trade-off between migration and residency (Hecht, Hard, Thrower, & Nichols, 2015). More recently, genomic studies have sought to evaluate molecular divergence between alternative resident and migratory ecotypes within salmonid species in an attempt to characterize the underlying genetic basis for migration.…”
Section: Introductionmentioning
confidence: 99%
“…In sympatry, freshwater residents may be genetically distinctive, inhabiting headwater streams (Narum et al 2008), or they may interact widely, effectively as a single population (Christie et al 2011;Courter et al 2013). In some instances, resident × resident crosses produce the anadromous life history form (Riva Rossi et al 2007;Christie et al 2011;Hecht et al 2015), but these crosses exhibit an exceedingly low adult return rate (Thrower et al 2004). On the other hand, allopatry presents a simpler relationship.…”
mentioning
confidence: 99%